Perbandingan Hasil Belajar PAI Sebelum dan Sesudah Pembelajaran Kooperatif Terhadap Pemahaman Siswa di Kelas VIII MTs Hubbul Wathon Sangatta Selatan - Abdulloh Edo; Ramdanil Mubarok; Miftakhul Rizal Mubaidillah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to determine the effectiveness of the implementation of cooperative learning methods on learning outcomes and students' understanding of Islamic Religious Education (IRE) subjects for Class VIII at MT Hubbul Wathon Sangatta Selatan. This study uses a quantitative method with a quasi-experimental research type using a non-equivalent control group design. The study population was 48 students of class VIII A and VIII B, with a sample size of 44 students, each class consisting of 22 students from the experimental class and the control class. Data collection techniques were carried out through tests (pre- and post-tests), observation, and recording. Data analysis used descriptive statistics, normality tests, homogeneity tests, N-Gain tests, and hypothesis tests (t-tests). The results showed that the average learning outcomes of students in the experimental class increased from 61.14% in the previous class to 84.09% in the next class, while in the control class increased from 63.41% to 77.73%. The results of the normality test showed that the data were normally distributed and the homogeneity test showed that the variances of the two groups were identical. The t-test results showed a significance value of 0.000 < 0.05, so it can be concluded that there is a significant difference between the experimental class and the control class. Thus, the cooperative learning method has a positive and effective effect in improving student learning outcomes and understanding in the Islamic Religious Education subject for Class VIII MT Hubbul Wathon Sangatta Selatan.